A RTP em ambiente digital: dos anos 90 à atualidade – um enquadramento teórico - Cádima, Francisco Rui (RIHC. Revista Internacional de Historia de la Comunicación, 2019)
This paper results from our communication to the 2019 AsHisCom Congress, which was focused on a more specific analysis of RTP’s website – the Portuguese public television. We draw on a paper meanwhile published in Portugal, and already available online (Cádima, 2019). But a significant part of the communication comprised some new issues related to the state of the art and the theoretical framework that allowed us to make this analysis of the evolution of RTP’s website over the last twenty years (1998-2018). This paper has to do with that other part of the study, i.e., with an analytical basis and a theoretical context. We end it with an approach to the preservation and an archival policy for the Web, as we have found in the research that a significant heritage has been consecutively lost and will continue to be lost if no assertive action is taken on this issue. This paper is also a warning for this dramatic loss of online content that occurs since the creation of the Web.